Eksplorasi Tanah Terracotta dengan Iron Oksida dalam Pembuatan Produk Keramik Tana Ampo: Eksplorasi Tanah Terracotta dengan Iron Oksida dalam Pembuatan Produk Keramik Tana Ampo - Kariada Pramana, I Komang; Arimbawa, I Made Gede; Artayani, Ida Ayu Gede (Pusat Penerbitan LPPM ISI Bali, 2025)
Ceramics is a unique art medium due to its reliance on high-temperature firing at every stage of its formation. Generally, ceramics are objects made from clay and fired to achieve specific forms and characteristics. The development of ceramic art has progressed significantly in recent years, particularly in terms of technique, materials, and supporting tools. In Bali, especially in tourist areas, the ceramic industry has flourished. However, this growth contrasts with the situation in Singaraja, which is more recognized for its traditional glass painting, wood carving, and earthenware crafts. This disparity motivated the author to explore ceramic art through the at Tana Ampo Pottery Studio in Sukawati, Gianyar. The author focused on three main aspects during the internship: (a) the development of the ceramic business at Tana Ampo Pottery Studio, (b) the ceramic forming and creation process, and (c) collaborative approaches in artistic production. The internship involved a collaborative method that included direct observation, literature review, and experimentation with local soil materials combined with iron oxide. The aim was to create a new clay character distinct from commercial clay. The outcome resulted in five ceramic artworks: three wall installations and two three-dimensional pieces, with stone-like visual characteristics in both color and texture. These works integrated Northern Balinese ornament motifs and wayang (shadow puppet) character expressions to reflect and strengthen local identity through artistic expression.